Forord - Tranekjær, Louise; Risager, Karen; Krogsgaard Svarstad, Lone; Jacobsen Perez , Susanne; Sonne Jakobsen, Karen; Kristjansdottir, Bergthora; Daryai-Hansen, Petra; Silvia Fernandez , Susana; Frederiksen, Karen-Margrete; Maslo, Elina; Meidell Sigsgaard, Anna-Vera (Sprogforum. Tidsskrift for sprog- og kulturpædagogik, 2019)
Resumé